Analisis Alih Kode Dan Campur Kode Dalam Film Ngeri – Ngeri Sedap Karya Bene Dion - Grasella Rasmaria Br.Damanik; Linda Ayu Kartika; Ika Febriana (Universitas Katolik Widya Karya Malang, 2023)
This study aims to analyze the use of language in the film Ngeri-Ngeri Sedap by Bene Dion. This study focuses on the analysis of code switching and code mixing contained in the film. The film that is raised in this study has a background in Batak culture with a typical Batak dialect because this film was produced in an area that is still thick with Batak culture, namely the area on the outskirts of Lake Toba. Apart from the Batak and Indonesian languages, this film also features several other languages, namely Javanese and Sundanese. Language is a tool for learning and thinking, every activity carried out by humans generally requires language in the process of carrying out daily activities. Language is often influenced by the situation, background and people we talk to. The method used in this research is descriptive qualitative method. The data and data sources collected are in the form of words. The data collection technique in this study is the observation and note taking technique. The listening technique in this study was carried out by listening to the speeches of the characters in the dialogues in the film. The results of this study are 5 conversational sentences containing code switching elements and 16 sentences containing code mixing elements.